2021
DOI: 10.15252/embr.202052145
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with the CCT chaperonin complex limits APOBEC3A cytidine deaminase cytotoxicity

Abstract: The APOBEC3 cytidine deaminases are implicated as the cause of a prevalent somatic mutation pattern found in cancer genomes. The APOBEC3 enzymes act as viral restriction factors by mutating viral genomes. Mutation of the cellular genome is presumed to be an off‐target activity of the enzymes, although the regulatory measures for APOBEC3 expression and activity remain undefined. It is therefore difficult to predict circumstances that enable APOBEC3 interaction with cellular DNA that leads to mutagenesis. The AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 89 publications
(143 reference statements)
0
13
0
Order By: Relevance
“…Consistent with the proteomics results of the previous study, in our hands the CCT complex binding is specific to A3A and does not co-purify with other A3 proteins. A3C shares some functional overlap with other A3 proteins including mRNA and ncRNA metabolic processes ( Figure 1E ) (58). The top A3C-specific functional enrichment is the Replication Protein A (RPA) complex, a heterotrimeric complex that binds to ssDNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with the proteomics results of the previous study, in our hands the CCT complex binding is specific to A3A and does not co-purify with other A3 proteins. A3C shares some functional overlap with other A3 proteins including mRNA and ncRNA metabolic processes ( Figure 1E ) (58). The top A3C-specific functional enrichment is the Replication Protein A (RPA) complex, a heterotrimeric complex that binds to ssDNA.…”
Section: Resultsmentioning
confidence: 99%
“…protein folding, with A3B, A3D, and A3F, it is for different complexes and specific proteins (PDCL3, PHLP, TXND9, TCPA, TCPH, and TCPZ) related to protein folding functions ( Figure S4C ). The A3A-specific functional enrichment is for PDCL and TRiC/CCT in G-protein beta folding, and in a recent study it was shown that A3A interaction with the CCT complex inhibits its deaminase activity (58). Consistent with the proteomics results of the previous study, in our hands the CCT complex binding is specific to A3A and does not co-purify with other A3 proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Suppression of A3 mRNA transcription provides the main protective measure against somatic mutagenesis, although A3B and A3A transcription is upregulated in response to DNA replication stress, an early sign of cellular transformation and viral infection ( Kanu et al, 2016 ; Oh et al, 2021 ). A3A activity also appears to be regulated by binding partners that suppress catalytic activity, such as Human Tribbles 3 or chaperonin-containing TCP-1 (CCT) complex ( Aynaud et al, 2012 ; Green et al, 2021 ). A3H Hap I is ubiquitinated in cells, and the resulting short half-life decreases its catalytic activity ( Chesarino and Emerman, 2020 ).…”
Section: Introductionmentioning
confidence: 99%